Golden jackal expansion in Europe - Krofel, Miha; Giannatos, Giorges; Ćirović, Duško; Stoyanov, Stoyan; Newsome, Thomas M. (Associazione teriologica italiana, 2017)
Top-down suppression by apex predators can limit the abundance and spatial distribution of mesopredators. However, this phenomenon has not been studied over long time periods in humandominated landscapes, where the strength of this process might be limited. Here, we used a multiscale approach to analyse interactions between two canids in the human-dominated landscapes of Europe. We tested the hypothesis that the range expansion of golden jackals (Canis aureus) was triggered by intensive persecution and resulting decline of the apex predator, the grey wolf (Canis lupus). To do so, we (1) reviewed literature to reconstruct the historic changes in the distribution and abundance of the two canid species on the continental scale, (2) analysed hunting data patterns for both species in Bulgaria and Serbia, and (3) surveyed jackal persistence in eight study areas that became re-colonized by territorial wolves. The observed trends were generally consistent with the predictions of the mesopredator release hypothesis and supported the existence of top-down suppression by wolves on jackals. We observed inverse patterns of relative abundance and distribution for both canid species at various spatial scales. In most (seven out of eight) cases of wolf re-colonization of jackal territories, jackals disappeared or were displaced out or to the periphery of the newly established wolf home-ranges. We suggest that wolf extermination could be the key driver that enabled the expansion of jackals throughout Europe. Our results also indicate that topdown suppression may be weakened where wolves are intensively persecuted by humans or occur at reduced densities in human-dominated landscapes, which has important management implications and warrants further research.